"A Vicious Cycle of Disempowerment": The Relationship Between Teacher Morale, Pedagogy, and Agency in an Urban High School. Issue 1 (January 2020) - Dunn, Alyssa Hadley
Background/Context: This research is framed by theories of teacher morale and teacher empowerment and contributes to the literature on neoliberal educational policies and teacher burnout and attrition. Purpose and Research Questions: The purpose of this study is to understand the intersections of teachers' experiences with neoliberal policies, at one high school in the urban south. The research questions include: (1) How is the morale of exceptional urban teachers affected by the contextual factors of a neoliberal school climate? (2) How does their morale relate to teachers' reports of their pedagogy? Research Design: This study utilized a qualitative case study design and, in addition to traditional analytic methods used in case studies, drew on grounded theory methodology. I collected quantitative data from approximately 30 staff members in the form of two surveys and qualitative data from eight focal participants. These participants were all (1) veteran teachers, (2) recognized as strong/exceptional teachers according to both neoliberal and non-neoliberal indicators, and (3) represented a diversity of other identity markers. My analysis here focuses on the qualitative data, and I use the quantitative results as a way to contextualize the data of my eight focal participants. Types of qualitative data include: interviews (semi-structured), a focus group, participant observations (of meetings at the district and school level), document analysis (of district-produced documents, school newspaper articles, local newspaper articles, and teachers' written reflections), and researcher journals and memos. Findings/Results: Results indicate that: (1) Morale is influenced by a variety of contextual factors at multiple levels, and being in a "good" school or being labeled an "exceptional" educator is not enough to keep one from feeling the effects of disempowerment brought about by top-down mandates, and (2) Teachers overwhelmingly reported that low morale impacted their view of their own pedagogy, contributing to a "vicious cycle" of low morale, disempowerment, and less effective pedagogy. The focal participants, even though they were hailed as successful educators, felt discouraged and unable to maintain quality pedagogy because of restrictive educational policies. Thus, I argue that educational policies at the school, district, state, and national level significantly decrease teachers' morale and have a negative influence on their perception of their pedagogy. In a vicious cycle, low morale makes them feel like less effective teachers, and their belief that they are less effective lowers their morale.